Performances of Galois sub-hierarchy-building algorithms - Arévalo, Gabriela Beatriz; Perrot, Guillaume; Sigayret, Alain; Berry, Anne; Huchard, Marianne (2007)
The Galois Sub-hierarchy (GSH) is a polynomial-size representation of a concept lattice which has been applied to several fields, such as software engineering and linguistics. In this paper, we analyze the performances, in terms of computation time, of three GSH-building algorithms with very different algorithmic strategies: Ares, Ceres and Pluton. We use Java and C++ as implementation languages and Galicia as our development platform. Our results show that implementations in C++ are significantly faster, and that in most cases Pluton is the best algorithm. Keywords: Galois Sub-hierarchy, AOC-Poset, Performance Analysis.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 10-03-2008)
Formal concepts analysis. 5th International Conference, ICFCA 2007, Clermont-Ferrand, France, February 12-16, 2007. Proceedings. Lecture Notes in Computer Science Volume 4390, p. 166-180. Springer, 2007.
Keywords: ALGORITMOS; ANÁLISIS DE RENDIMIENTO; INGENIERÍA DE SOFTWARE